Survey of environmental management in ports of entry on land borders of Thailand - ถมังรักษ์สัตว์ มนจิรา; ทิมพงษ์ อรทัย; ทุเครือ อัจฉรา (Disease Control Journal, 2018)
This study aims to survey the current circumstances and challenges related to environmental management in all existing 33 ports of entry for the development of environmental management standards for the ports of entry situated on land borders across the country. The study was conducted from April to August 2017 by mailing a questionnaire to the personnel responsible for environmental management in each port of entry. The study also included interviewing the personnel, observing, and surveying the areas to determine environmental problems in eight ports of entry located along the land borders with four neighboring countries, i.e. Laos, Cambodia, Malaysia, and Myanmar. Each of these eight ports of entry had either the highest or the lowest numbers of people crossing the border. Of the total 33 ports of entry, 26 (78.8%) participated in the study. Of the 26 participating ports of entry, 4 (15.4%) were found to collectively have 12 food shops, of which 5 (41.7%) achieved food sanitation standards implemented by the Department of Health, Ministry of Public Health, while there were no reports on food sanitation standards for the remaining 7 (58.3%). Of these 26 study ports, only 26.9% had a public piped water system, which is run by the Provincial Waterworks Authority (PWA). About 42.3% of them were found to utilize running water from surface/mountain water resources, and 30.8% utilized tap water from groundwater supply. With the exception of PWA-supplied running water, most of other water supply systems had no water treatment system in place. Garbage management services by the local administration organizations were most frequently used by 69.2% of the ports and 88.5% reported no problems with infectious waste management. The main problems relating to public toilets were uncleanliness and insufficiency. Only 57.7% of the ports had public toilets for the disabled/the elderly. Most (76.9%) of the ports did not have proper management of waste water and sewage disposal. All the personnel needed appropriate guidelines for environmental management and standards. It is essential for the committee on the ports of entry to develop a sustainable environmental management strategy.